Genome-scale reconstructions of the mammalian secretory pathway predict metabolic costs and limitations of protein secretion - Jahir M. Gutierrez (Nature Portfolio, 2020)
The secretory pathway is used in the production of most biopharmaceuticals, but the associated biosynthetic costs are little understood. Here, the authors integrate the core secretory pathway into genome-scale metabolic models of human, mouse, and CHO cells, enabling in silico analysis.